Blood and Fire : Godly Love in a Pentecostal Emerging Church. - Poloma, Margaret M. (NYU Press, 2008)
What does it mean to live out the theology presented in the Great Commandment to "love God above all and to love your neighbor as yourself"? In Blood and Fire, Poloma and Hood explore how understandings of godly love function to empower believers. Though godly love may begin as a perceived relationship between God and a person, it is made manifest as social behavior among people. Blood and Fire offers a deep ethnographic portrait of a charismatic church and its faith-based ministry, illuminating how religiously motivated social service makes use of beliefs about the nature of God's love. It t.